Predicting self- Harming in Adolescent Girls based on Irrational Beliefs, Emotional Dysregulation Regulation and Social Support - elham mostashari; amir-houshang mehryar; Nadereh Sohrabi; Hojatollah Javidi (پژوهشنامه مددکاری اجتماعی, 2021)
The aim of this study was to predict self-harming in adolescent girls based on irrational beliefs, emotional dysregulation and social support. The statistical population of this descriptive-correlational study included all 12- to 19-year-old self-harming female students in Tehran in the academic year 2019 who they were studying in public schools, from which 150 people who scored a standard deviation above the average in the Inventory of Statements About Self-Injury were selected using multi-stage cluster sampling. Data were collected using the Jones (1968) Irrational Beliefs Questionnaire, the Gratz and Roemer (2004) Disacceptance of Emotional Responses Scale, and the Zimet et al.'s (1988) and Multidimensional Scale of Perceived Social Support. There is a positive and significant relationship between helplessness against change, expecting approval from others, avoiding problems and emotional irresponsibility with self-harming; there is a positive and significant relationship between non - acceptance of emotional responses, limited access to emotion regulation strategies during pressure, difficulty in performing targeted behaviors during pressure, lack of awareness, emotional clarity and difficulty in controlling shocks under pressure with self-harming and there is a positive and significant relationship between between family, community and family with self-harming (p<0.05). In addition, components of expectations from others are the ability, limited access to emotional regulation strategies, the difficulty of controlling the ability to predict self - harming (p<0.05). This study seems to have an important role in the relationship between self - harming with irrational beliefs, emotional dysregulation and social support in adolescent girls.